Effect of Urea Fertilizer on the Biological Nitrification Process in Soils of Different Textures and Locations - Hamid Mohsin Ghyadh; Mohammed Saeed Haran (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
An experiment was conducted to study the effect of adding different levels of urea fertilizer (ppm Urea-N0,75,150,225,300) on the effectiveness of bio-nitrification in the studied soil. The study treatments for this experiment were (4 soils of different textures and locations × 5 urea levels × 3 replicates) in an experiment in which a completely randomized design (CRD) was used. It was incubated at laboratory temperature (25°C) for 40 days, during which the amount of formed nitrates and remaining ammonium was measured every ten days, noting the replacement of lost water every two days. The highest percentage of formed nitrates (39.8%) was recorded from the ammonium added to Basrah soil after ten days of incubation, followed by Kut soil, which recorded 29.8%, and less than that in Shatra soils (24.2%) and Fajr soils (23.7%). After that, the efficiency of nitrification decreased in the subsequent incubation periods up to 40 days of incubation.The percentage of ammonium remaining from urea added to the soil was recorded after the four incubation periods at 20.0 ppm (when adding 225 ppm urea to the Qurna soil), which differed significantly from the rest of the studied soils.